Pengaruh Kompetensi Sumber Daya Manusia, Gaya Kepemimpinan dan Pemanfaatan Teknologi Informasi terhadap Kualitas Laporan Keuangan Gereja Paroki Wilayah Kota Maumere - Mariano Riskynanta Moa Maro; Wilhelmina Mitan; Siktania Maria Dilliana (Jurnal Mutiara Ilmu Akuntansi, 2024)
The aim of this research is to determine the influence of human resource competence, leadership style and use of information technology on the quality of financial reports of Parish Churches in the Maumere City area. This research uses an associative quantitative approach. The population in this study was the Financial Council taken from 5 Parish Churches in Maumere City, namely 32 respondents. The sampling method used in this research was saturated sampling so that the number of samples obtained was 32 respondents. The data collection process was carried out by distributing questionnaires to respondents, where the research instrument used a Likert scale. The data analysis technique used in this research uses a multiple linear regression analysis model with the help of the IBM SPSS Statistics 26 program. The results of this research show that the variables of human resource competency, leadership style and the use of information technology partially and simultaneously have a significant effect on the quality of the Church's financial reports. Maumere City Parish.